Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

Propylparaben exposure may impair uterine decidualization via FDX1 downregulation and induce preeclampsia-like symptoms in mice - Xiaohui Li; Rui Fu; Huiyu Liu; Yuhan Cai; Cong Zhang (Reproductive Toxicology, 2026)

A study on the hydrodynamic performance and wake modulation effect of a twisted pre-swirl stator in a rim-driven thruster - Yi-Ming Hu; Cong Sun; Min Liu; Chun-Yu Guo; Pei-Rui Tang; Yu Zhao; Chao Wang (Ocean Engineering, 2026)

Effects of dietary Portulaca oleracea L. aqueous extract on growth performance, intestinal health and intestinal microflora of common carp (Cyprinus carpio) - Jing-Tong Huang; Cong-Fu Liu; Yu-Shi Cai; Li-Fang Li; Hai-Tao Zhao; Yan-Ping Yang; Rui-Fang Wang (Animal Feed Science and Technology, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Formation and magmatic evolution of the mangling plutonic complex in North Qinling, China - Rui-yang Liu; Shao-cong Lai (Acta Geochimica, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

Climatological characterisation and trends of extreme winds and their application to power transmission lines in China - Hongyu Wang; Cong Jiang; Feifei Mu; Kai Liu; Rui Mao; Xin Yin (Natural Hazards, 2026)

Diketopiperazines from marine-derived Exserohilum sp. M1-6 - Rui Xu; Jianjian Wang; Changyu Liu; Xuefang Yang; Minjun Chen; Zihan Jin; Shengyan Zheng; Peihai Li; Cong Wang; Shugeng Cao (Natural Product Research, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Ureolysis-driven sulfidogenic precipitation and pH enhancement for robust bioremediation of zinc-laden acid mine drainage - Cong Peng; Zhenyu Zhang; Zhendong Yang; Li Zeng; Huijun Xi; Zhenghua Liu; Huaqun Yin; Delong Meng; Yonghong Liu; I.A. Ibrahim; Hongjuan Sun; Ke Zhang; et al. (Journal of Environmental Chemical Engineering, 2025)

Preparation and characterization of Ag@MOF-Amomum tsaoko essential oil/waterborne polyurethane composite films for strawberry preservation - Yuyue Qin; Hongda Yu; Haiyan Chen; Yongliang Zhuang; Qiuming Liu; Rui Cui; Cong Zhang; Charles Brennan; Yuanxiang Huang (Food Control, 2025)

Synergistic charge separation and magnetic recovery in a noble-metal-free Fe3O4/TiO2/Bi photocatalyst for bromate reduction - Ying Xu; Shuili Yu; Zhiqiang Fan; Xingli Ji; Cong Huang; Zheng Xu; Rui Liu; Chao Jiang (Journal of Water Process Engineering, 2025)

Bismuth nanospheres enabling sacrificial-agent-free bromate photoreduction and total bromine mitigation for safer water treatment - Ying Xu; Shuili Yu; Zhiqiang Fan; Cong Huang; Lei Li; Rui Liu; Zheng Xu (Journal of Hazardous Materials, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Enhanced moisture tolerance and toluene oxidation activity of δ-MnO2 catalysts by Sn doping: Phase transition and surface protection - Yiming Li; Mengxia Xu; Rui Liu; Shuibo Wang; Taotao Sun; Zijun Yan; Cong Wan; Hongbo Yu; Haocheng Li; Haotian Li; Xudong Zhao; Kaijie Li; et al. (Fuel, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Subduction-induced crustal growth in the Neoproterozoic continental magmatic arc: Evidence from arc-type high-Mg# diorites and adakitic granitoids in the western Yangtze Block, South China - Rui-Yang Liu; Shao-cong Lai; Yu Zhu; Ren-Zhi Zhu; Min Liu; Jiang-Feng Qin; Fang-yi Zhang; Hang Yang (Precambrian Research, 2025)

Development of a new onset of film boiling model within the fouling layer - Xiaowen Wang; Maolong Liu; Rui Zhang; Tenglong Cong; Yao Xiao; Hanyang Gu (Annals of Nuclear Energy, 2025)

Adaptive neofunctionalization of ancestral CYP6SN2vB following duplication contributes to abamectin resistance in Chilo suppressalis Walker - Shuai Wang; Yuan Xie; Chong Liu; Jin-Wei Liu; Fang-Rui Guo; Song-Tao Qiao; Yu-Ji Xing; Shun-Fan Wu; Chris Bass; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2025)

Identification and bioactivity evaluation of ring-opening and lactone forms of enterolactone from sheep fed flaxseed cake - Cong-Cong Zhuang; Chun-Rui Liu; Hai-Yan Xu; Xin-Yue Yang; Dan-Dan Wu; Zhong Zheng; Li-Wei Wang; Zheng Liu; Chao-Mei Ma (Natural Product Research, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Research on Characteristics of the Hermite–Gaussian Correlated Vortex Beam - Rui Cong; Dajun Liu; Yan Yin; Haiyang Zhong; Yaochuan Wang; Guiqiu Wang (Journal of Marine Science and Engineering, 2025)
In this work, a new beam named the Hermite–Gaussian correlated vortex beam (HGCVB) is introduced. The intensity and coherence of this HGCVB in oceanic turbulence are analyzed. The results show that the HGCVB displays a splitting property during propagation, and the HGCVB can evolve into the array profile with hollow center beamlets. The results display that the evolution of the intensity of the HGCVB is manipulated by the coherence length δ0 and topological charge M. Meanwhile, the array distribution of coherence of the HGCVB in oceanic turbulence can evolve into a one-spot pattern on propagation. The results show that this HGCVB evolves from a Gaussian beam into a beam array composed of beamlets with hollow centers and may have a potential application in oceanic turbulence.

Heavy metal and metalloid source identification in lake and river sediment in the Honghu Watershed: Coupling land use analysis with RDA and PMF in central China - Yuanzheng Liu; Xiaoguo Chen; Xi Liu; Cong Wang; Lu Zhang; Rui Zhou; Zhi Wang; Xiaolong Huang (Journal of Soils and Sediments, 2025)

Analytical solutions of two-liner tunnels constructed in time-dependent plastic rocks considering loading-unloading stress paths - Hua-ning Wang; Qian Liu; Fei Song; Rui-cong Fu; Ming-jing Jiang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

A targeted reformulation of safflower oil: Enhancing anti-inflammatory potential and market competitiveness through ω3 enrichment - Rubab Arshad; Jiawei Wan; Tingyang Ai; Cong Yin; Yonghua Qin; Rui Qin; Jiao Liu; Hong Liu (Food Research International, 2025)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Deep Learning Approach for Hydraulic Support Anomaly Detection: Utilizing Convolutional Autoencoders and Dynamic Time Warping Technology - Xigui Zheng; Cong Wang; Chao Kong; Cancan Liu; Kai Zhan; Rui Xu (Rock Mechanics and Rock Engineering, 2024)

Tectonosedimentary patterns of multiple interacting source-to-sink systems of the permian Shanxi Formation, Ordos Basin, China: Insights from sedimentology and detrital zircon U-Pb geochronology - Dan Li; Lei Liu; Zhiwei Wang; Cong Hu; Hongde Chen; Shuyue Zhu; Rui Zhang; Fei Zhao (Marine and Petroleum Geology, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Number of denatured rigor cross-bridges determines the intracellular volume shrinkage in porcine muscle fibre under PSE-inducing condition - Cong Yin; Siyang Wu; Nan Yang; Tingyang Ai; Jiawei Wan; Qin Rui; Hong Liu; Hairong Xiong; Jiao Liu (Meat Science, 2024)

Development of a heat transfer model for the film boiling regime in a fouling layer - Xiaowen Wang; Rui Zhang; Maolong Liu; Tenglong Cong; Limin Liu; Li Liu; Hanyang Gu (Annals of Nuclear Energy, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Microbial response and spatial profiling of nitrite-producing denitrification granular sludge in-situ exposed to high nitrite stress - Jiarui Fan; Rui Du; Qingtao Liu; Cong Li; Yongzhen Peng (Chemical Engineering Journal, 2024)

Two birds with one stone: Gold “bridging” both nanozyme and immunosensor for sensitive double-response detection of T-2 toxin - Rui Shu; Sijie Liu; Cong Zhao; Xi Lan; Yuechun Li; Jianlong Wang; Nannan Qiu; Daohong Zhang (Chemical Engineering Journal, 2024)

Identification, characterization and hypolipidemic effect of novel peptides in protein hydrolysate from Protaetia brevitarsis larvae - Zong-Qi Zhang; Xin-Rui Ren; Jin Geng; Si-Cong Chen; Qing-Lei Wang; Chun-Qin Liu; Jin-Hua Xiao; Da-Wei Huang (Food Research International, 2024)

Electrospinning is a potential way for preparing edible plant protein-based nanofibers with porous surface using safflower seed meal - Yanling Yang; Chuang Peng; Dong Zeng; Zhengjie Yang; Xiaohu Wang; Shuang Zhang; Yucheng Bai; Lujing Kuang; Lizhi Guo; Yonghua Qin; Hairong Xiong; Jiawei Wan; et al. (Food Hydrocolloids, 2024)

Expansive microbial metabolic versatility and spatial biodiversity of anammox coupling with denitrification granular sludge under different feeding strategies - Cong Li; Rui Du; Qingtao Liu; Jiarui Fan; Yongzhen Peng (Chemical Engineering Journal, 2024)

CaO hydrated with ethanol solution for flue gas HCl immobilization. Part II: Influences of gas components - Rui Wang; Xiaoshuo Liu; Cong Chen; Yuqing Wang; Zhen Shen; Lei Meng; Xiaobing Gu; Changdong Sheng; Yufeng Duan (Fuel, 2023)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

Selenium speciation and volatile flavor compound profiles in the edible flowers, stems, and leaves of selenium-hyperaccumulating vegetable Cardamine violifolia - Yan Ma; Jinjing Yin; Jingyi Wang; Xin Liu; Jingren He; Rui Zhang; Shen Rao; Xin Cong; Yin Xiong; Muci Wu (Food Chemistry, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

Intrinsic reaction selectivity between gaseous HCl and SO2 over ethanol-hydrated CaO adsorbent in coal-fired flue gas dechlorination - Xiaoshuo Liu; Rui Wang; Xinze Geng; Ao Shen; Cong Chen; Yifan Xu; Xunlei Ding; Yufeng Duan; Shilin Zhao (Chemical Engineering Journal, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

CaO hydrated with ethanol solution for flue gas HCl immobilization. Part Ⅰ: Modification & dechlorination - Rui Wang; Xiaoshuo Liu; Cong Chen; Yuqing Wang; Zhen Shen; Lei Meng; Xiaobing Gu; Changdong Sheng; Yufeng Duan (Fuel, 2023)

Evaluation of sludge anaerobic fermentation driving partial denitrification capability: In view of kinetics and metagenomic mechanisms - Qingtao Liu; Cong Li; Jiarui Fan; Yongzhen Peng; Rui Du (Science of The Total Environment, 2023)

Enhanced recovery of germanium(IV) from zinc residue leachate by tartaric acid functionalized chitosan: Experiments and DFT calculation - Hongrui Xiang; Zhihui Yang; Xiaobo Min; Yanjie Liang; Cong Peng; Xiaoyun Liu; Rui Yuan; Qingwei Wang; Feiping Zhao (Hydrometallurgy, 2023)

Enlocking the high Zn2+-storage of conversion-type Te cathode by regulating the surface binding-interaction with graphene - Cong Guo; Shangjun Yi; Rui Si; Yixiao Wang; He Liu; Feng Yu; Jingfa Li (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Atmospheric ammonia in China: Long-term spatiotemporal variation, urban-rural gradient, and influencing factors - Jinyan Dong; Baojie Li; Yan Li; Rui Zhou; Cong Gan; Yongqi Zhao; Rui Liu; Yating Yang; Teng Wang; Hong Liao (Science of The Total Environment, 2023)

Impact of clayey sediment compaction on pore water evolution and the release of iron - Yanjun Liu; Teng Ma; Juan Chen; Ziqi Peng; Cong Xiao; Wenkai Qiu; Rui Liu; Yao Du (Applied Geochemistry, 2023)

‘Yunnan’ quince rootstock promoted flower bud formation of ‘Abbé Fetel’ pear by altering hormone levels and PbAGL9 expression - Liu Cong; Hutian Ling; Shanshan Liu; Azheng Wang; Rui Zhai; Chengquan Yang; Zhigang Wang; Lingfei Xu (Journal of Plant Physiology, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Metagenomics-based interpretation of selective bioaugmentation promoting partial-denitrification coupling with anammox process reactivation in suspended sludge system - Cong Li; Qingtao Liu; Jiarui Fan; Yongzhen Peng; Rui Du (Chemical Engineering Journal, 2023)

The gluten structure, starch digestibility and quality properties of pasta supplemented with native or germinated quinoa flour - Bao Xing; Zhuo Zhang; Manli Zhu; Cong Teng; Liang Zou; Rui Liu; Lizhen Zhang; Xiushi Yang; Guixing Ren; Peiyou Qin (Food Chemistry, 2023)

Azospirillum Endophyticum sp. nov., an Endophyte of Paris Polyphylla Smith var. Yunnanensis - Peng-Chao Zhan; Rui-Feng Mao; Cong-Jian Li; Zhen Zhang; Jing-Ran Liu; Mei Tang; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2023)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

Impact process of the aquitard to regional arsenic accumulation of the underlying aquifer in Central Yangtze River Basin - Cong Xiao; Teng Ma; Yao Du; Yanjun Liu; Rui Liu; Dongtao Zhang; Juan Chen (Environmental Geochemistry and Health, 2021)

Allelopathy confers an invasive Wedelia higher resistance to generalist herbivore and pathogen enemies over its native congener - Shan-Shan Qi; Yan-Jie Liu; Zhi-Cong Dai; Ling-Yun Wan; Dao-Lin Du; Rui-Ting Ju; Justin S. H. Wan; Stephen P. Bonser (Oecologia, 2020)

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

Effects of Exogenous Application of Melatonin on Quality and Sugar Metabolism in ‘Zaosu’ Pear Fruit - Jianlong Liu; Rongrong Yue; Min Si; Meng Wu; Liu Cong; Rui Zhai; Chengquan Yang; Zhigang Wang; Fengwang Ma; Lingfei Xu (Journal of Plant Growth Regulation, 2019)

Comparison of volatile profiles and bioactive components of sun-dried Pu-erh tea leaves from ancient tea plants on Bulang Mountain measured by GC-MS and HPLC - Wen-jie Zhang; Cong Liu; Rui-juan Yang; Ting-ting Zheng; Miao-miao Zhao; Li Ma; Liang Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Review: Water–rock interactions and related eco-environmental effects in typical land subsidence zones of China - Teng Ma; Yao Du; Rui Ma; Cong Xiao; Yanjun Liu (Hydrogeology Journal, 2018)

Isolation, chemical characterization, and immunomodulatory activity of naturally acetylated hemicelluloses from bamboo shavings - Ju-qing Huang; Rui-ting Qi; Mei-rong Pang; Cong Liu; Guang-yu Li; Ying Zhang (Journal of Zhejiang University-SCIENCE B, 2017)

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

Acute toxicity and chemical evaluation of coking wastewater under biological and advanced physicochemical treatment processes - Ma Dehua; Liu Cong; Zhu Xiaobiao; Liu Rui; Chen Lujun (Environmental Science and Pollution Research, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Bioaugmentation with isolated strains for the removal of toxic and refractory organics from coking wastewater in a membrane bioreactor - Xiaobiao Zhu; Rui Liu; Cong Liu; Lujun Chen (Biodegradation, 2015)

Screening of Inherited Metabolic Disorders in Infants with Infantile Spasms - Xiao-Ming Liu; Rui Li; Sheng-Zhi Chen; Yan Sang; Jiao Chen; Cong-Hai Fan (Cell Biochemistry and Biophysics, 2015)

Assessment of combined antiandrogenic effects of binary parabens mixtures in a yeast-based reporter assay - Dehua Ma; Lujun Chen; Xiaobiao Zhu; Feifei Li; Cong Liu; Rui Liu (Environmental Science and Pollution Research, 2014)

Isolation and Characterization of the Cold-Induced Phyllostachys edulis AP2/ERF Family Transcription Factor, peDREB1 - Lei Liu; Xiao-Lu Cao; Rui Bai; Na Yao; Lu-Bin Li; Cong-Fen He (Plant Molecular Biology Reporter, 2012)